2012
DOI: 10.4018/ij3dim.2012100105
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Whole Life Cycle Costs When Utilising Building Information Modelling Technologies

Abstract: Building Information Modelling (BIM) is now being increasingly used as a technology tool to assist design

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Several research studies have categorized the factors that impact BIM implementation in the construction industry into multiple categories and classes. For instance, Smith (2014), Kehily (2016) and Abubakar et al (2014) have studied factors affecting BIM from various perspectives including drivers , barriers , challenges and other factors associated with people , processes , information and technology . Additionally, Ramilo and Embi (2014) categorized the barriers to digital innovation adoption into organizational , process , financial , psychology and governmental barriers .…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Several research studies have categorized the factors that impact BIM implementation in the construction industry into multiple categories and classes. For instance, Smith (2014), Kehily (2016) and Abubakar et al (2014) have studied factors affecting BIM from various perspectives including drivers , barriers , challenges and other factors associated with people , processes , information and technology . Additionally, Ramilo and Embi (2014) categorized the barriers to digital innovation adoption into organizational , process , financial , psychology and governmental barriers .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Popov et al (2010) suggested that BIM has become a solution to many construction inefficiencies by providing a framework to share information among various project phases over the entire life cycle of projects. Smith (2014) and Kehily (2016) recognized BIM's benefits in enabling fully integrated project delivery and simulating construction activities in a virtual environment. Moreover, studies have shown that BIM supports individuals in working together by facilitating data sharing (Fung et al , 2014; Isikdag and Underwood, 2010; Aibinu and Venkatesh, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in information technology have led to a new breed of computer-based tools. Artificial neural networks (ANNs) are one of the best and most widely utilised tools in the development of prediction models in different fields [8,9]. These networks have been used in the development of many applications for predicting energy consumption [3,[10][11][12][13][14][15][16].…”
Section: Literature Reviewmentioning
confidence: 99%
“…BIM is used comprehensively in the building industry, especially for the life-cycle costing (LCC) of construction buildings. Kehily et al [8] revealed a generic template that could be integrated with a 4D BIM process to consider certain documented barriers for the successful application of LCC in practice. William et al [9] studied the challenges in estimating costs using BIM, while Shin and Cho [17] evaluated the usability of BIM to carry out life-cycle analysis (LCA) and LCC in the early stages of a construction project.…”
Section: Literature Reviewmentioning
confidence: 99%
“…BIM enables stakeholders to make educated decisions regarding a building's design, construction, and operation through the integration of diverse data sources with modelling, hence providing ability to foresee critical scenarios [9][10][11]. The use of BIM to optimise LCC entails creating a centralised digital model that captures all critical information about a structure, from conception to demolition [12][13][14]. This model functions as a dynamic database that stakeholders can access at various stages of the building's life.…”
mentioning
confidence: 99%